Adoptive parents' evaluation of expectations and children's behavior problems: The mediational role of parenting stress and parental satisfaction. (May 2018) - Santos-Nunes, Marta; Narciso, Isabel; Vieira-Santos, Salomé; Roberto, Magda Sofia
Abstract: Despite empirical evidence of the impact of parents' expectations on the success of adoption, few studies have specifically focused on this subject. This study aimed to test the impact of parents' evaluation of expectations on their child's behavioral problem by investigating a sequential mediation effect of parenting stress and parental satisfaction. The sample included 116 adoptive parents (31–60 years) of children (6–12 years) who had been part of the family for, at least, two years. The Portuguese versions of the Parenting Stress Index-Short Form and the Strengths and Difficulties Questionnaire-Parents version were used to measure the level of parenting stress and the children's behavioral difficulties, respectively. Moreover, specific indexes of parents' evaluation of expectations and satisfaction were used. The results supported the sequential mediation model proposed, highlighting the importance of fostering the development of accurate expectations. Highlights: Adoptive parents' expectations contributes to the perception of children's behavioral problems, parenting stress and parental satisfaction. Adoptive parents' parenting stress mediated the relationship between the evaluation of expectations and children's behavioral problems. Adoptive parents' parental satisfaction mediated the relationship between the evaluation of expectations and children's behavioral problems. Adoptive parents' parenting stress and parental satisfaction are sequential mediators of the link between parents' expectations and children's behavioral problems.